Pengenalpastian Variasi Luar Terhadap Pencapaian Pelajar Melalui Kawalan Proses Berstatistik (KPB) - Zakiah, Hashim (2003)
To compete in today’s challenge in education industry and to achieve a world class university, we must produce a world class quality product such as quality graduates. In order to assure our teaching and assessments achieve the goal of producing quality graduates, we have to be sure that the teaching and assessment process is not affected by student’s background, assessment factor from the viewpoint of whether the question is extremely easy or extremely difficult and lecturer’s teaching factor. So, we have to perform some controls to detect the presence of these factors. The purpose of this study is to introduce a process control that detects the presence of these factors, which may affect the assessment process.